The Tambo Tuanku Imam Bonjol Manuscript as an Authentic Historical Source of the Padri War (1803-1837) - Haris Priyatna; Dedi Supriadi; Asep Achmad Hidayat; Yan Nurcahya (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2026)
After the Padri War (1803-1837), Tuanku Imam Bondjol was exiled by the Dutch colonial government to Minahasa and Manado. During his exile in Manado, his son, Naali Sutan Caniago, who accompanied Tuanku Imam Bondjol during his exile, wrote a manuscript about his father's struggle. This manuscript is called the Tambo Tuanku Imam Bondjol Manuscript, which is a single manuscript (codex unicus). In general, this manuscript contains a summary of the history of the Padri War in West Sumatra in the 19th century. It contains Tuanku Imam Bondjol's memoirs, his thoughts, and notes on the Padri war. In this study, the Tambo Tuanku Imam Bondjol manuscript is examined using philological and historical methods. This manuscript has been transliterated and translated by Safnir Abu Naim, However, this study will trace the philological stages carried out on the Tambo Tuanku Imam Bondjol manuscript to demonstrate its originality and authenticity. The problem examined in this study is how the Tambo Tuanku Imam Bondjol manuscript stands as a historical source of the Padri War. To that end, a textual study of the translation of the manuscript was conducted using the Critical Discourse Analysis (CDA) method modeled by Teun A. Van Dijk. This study also uses the Historical Method with the ultimate goal of compiling a historiography of the struggle of Tuanku Imam Bondjol and the Padri War. From the results of the study, it is concluded that the Tambo Tuanku Imam Bondjol manuscript is an authentic source of the Padri War, a first-hand historical source originating from indigenous records. Before the discovery of this manuscript, sources for the Padri War were generally only from colonial archives.